HUBUNGAN ADVERSE CHILDHOOD EXPERIENCES DENGAN FATHER INVOLVEMENT PADA AYAH YANG MEMILIKI USAHA DI RUMAH DI KOTA BUKITTINGGI - Dara Siska Amelia; Zulian Fikry (EDUPEDIA, 2026)
This study aims to examine the relationship between adverse childhood experiences (ACEs) and father involvement among fathers who run home-based businesses in Bukittinggi City. The subject of this study consisted of 97 fathers who operate businesses from their homes, have longer working hours at home, and have dependent children, selected through purposive sampling. This study employed a quantitative correlational approach. Data were collected using the Inventory of Father Involvement (IFI) adapted by Fajriati & Kumalasari (2021) and the Adverse Childhood Experiences International Questionnaire (ACE-IQ) adapted by Rahapsari et al. (2021). Data were analyzed using Pearson correlation test after meeting the assumptions of normality and linearity. The results showed a significant negative relationship between ACEs and FI (r = -0.760, p < 0.001), indicating that the higher the exposure to adverse childhood experiences, the lower the level of paternal involvement in childcare. These findings suggest that physical proximity alone does not guarantee quality father involvement,and that early life experiences play a substantial role in shaping parenting behavior in adulthood.